Analysis of the Power Load when Finishing Very Precise Holes by Reaming Head MT3 - Sedlak, Josef; Jaros, Ales; Slany, Martin; Kouril, Karel; Majerik, Jozef; Barenyi, Igor (Manufacturing Technology Journal, 2018)
Design and technological development of cutting tools represents a fluent process that combines new knowledge from all usable technical branches with actual needs and development results of component base, production technology and machine tools. The main factors which nowadays accelerate the development of cutting tools are constantly increasing demands to improve efficiency and productivity while reducing operation costs, the application of hard machinable materials, environmental protection issues, health and growing demands for greater safety. The article deals with methodology of measurement and evaluation of cutting forces and cutting torque at a special reaming head MT3 from FINAL Tools Inc. Solution of force loading during reaming by these modern tools enable to analyse the causes of cutting tool deficiencies starting from coating suitability up to weaknesses in their design. The article also analyses the significance of the reaming process from the reaming view point using a process liquid, including a tool life analysis combined with the tool wear.
Keywords: Reaming Head; MT3; Finishing; Precise Holes; Force Loading